Diseño de modelo de optimización del nodo productivo del café en la provincia de Lengupá (Boyacá) (2020)
The present degree project aims to make known the importance of seeking the optimization of production processes supported by the use of computer tools, in this case through a simulation through the use of Flexsim Manufacturing Software, which presents quantitative analysis instruments that facilitate decision-making and directing them. The research was carried out in the productive node of small coffee growers in the Province of Lengupá (Boyacá) which present an attractive trade in exotic coffee very different from the coffees found in the common market, however this area presents Very few studies and information regarding the form of cultivation, process and treatment of the grain, for which the authors of this work present a characterization of the area, some optimization scenarios and a series of recommendations related to processes related to traditional coffee cultivation. supported by the material obtained in interviews, surveys and visits to leading municipalities in production in this region. For the search for optimization, some factors immersed in this productive node were defined, parameterizing them and generating a simulation model based on the real field of work action. Finally, some results were obtained which were analyzed in order to identify improvements, propose them, develop them and deliver them to small coffee growers. However, one of the purposes of the development of this project is to provide advances in the research carried out by the Antonio Nariño University in this sector hand in hand with its research groups.